Sprachwissenschaft im Fokus. Positionsbestimmungen und Perspektiven - Eichinger, Ludwig (Jahrbuch des Instituts für Deutsche Sprache, 2015)
The contributions of this volume, celebrating the 50th anniversary of Institut für deutsche Sprache, discuss current trends in grammar research and grammaticography, lexicology and lexicography, spoken language research, as well as corpus and computer linguistics. In addition, they provide an overview of the current status of linguistic research and possible new fields of investigation.